2020
DOI: 10.1186/s12935-020-01310-y
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0000284 plays an oncogenic role in the progression of non-small cell lung cancer through the miR-377-3p-mediated PD-L1 promotion

Abstract: Background: Circular RNAs (circRNAs), a subgroup of non-coding RNAs, are recognized as pivotal mediators in various types of cancers. CircRNA_0000284 (circ_0000284) was manifested to participate in the development of nonsmall cell lung cancer (NSCLC). The novel functional mechanism of circ_0000284 in NSCLC was investigated in our current study. Methods: We exploited quantitative real-time polymerase chain reaction (qRT-PCR) to analyze the relative RNA (circRNA, miRNA and mRNA) expression. The assessment of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…Recent emerging evidence has demonstrated that circRNAs are closely associated with tumor initiation and progression (17)(18)(19)(20). Firstly, deregulation of circRNAs has been confirmed in many types of cancers, including breast cancer (21,22), lung cancer (23,24), prostate cancer (25), colorectal cancer (26), gastrointestinal cancers (27), ovarian cancer (28), thyroid cancer (29), gynecologic cancers (30), and hepatocellular carcinoma (31); Secondly, some circRNAs have been demonstrated to play either oncogenic (32,33) or tumor suppressive (34,35) roles in affecting multiple cancer hallmarks, including deregulating cellular energetic, self-sufficiency in growth signals, insensitivity anti-growth signals, evading cell death, limitless replicative potential, substained angiogenesis, tissue invasion and metastasis (36,37). Moreover, given the facts that circRNAs are more resistant to exoribonuclease degradation due to their lack of free 5′-and 3′-ends (38) and are abundant in body fluids, such as saliva, blood, and urine (39-41), they have been increasingly recognized as promising tumor biomarkers (42).…”
Section: Introductionmentioning
confidence: 99%
“…Recent emerging evidence has demonstrated that circRNAs are closely associated with tumor initiation and progression (17)(18)(19)(20). Firstly, deregulation of circRNAs has been confirmed in many types of cancers, including breast cancer (21,22), lung cancer (23,24), prostate cancer (25), colorectal cancer (26), gastrointestinal cancers (27), ovarian cancer (28), thyroid cancer (29), gynecologic cancers (30), and hepatocellular carcinoma (31); Secondly, some circRNAs have been demonstrated to play either oncogenic (32,33) or tumor suppressive (34,35) roles in affecting multiple cancer hallmarks, including deregulating cellular energetic, self-sufficiency in growth signals, insensitivity anti-growth signals, evading cell death, limitless replicative potential, substained angiogenesis, tissue invasion and metastasis (36,37). Moreover, given the facts that circRNAs are more resistant to exoribonuclease degradation due to their lack of free 5′-and 3′-ends (38) and are abundant in body fluids, such as saliva, blood, and urine (39-41), they have been increasingly recognized as promising tumor biomarkers (42).…”
Section: Introductionmentioning
confidence: 99%
“…The circRNA/microRNA (miRNA)/messenger RNA (mRNA) network is an important pathway for circRNA in regulating lung cancer progression 8 . Previous studies have reported that many circRNAs (like circ_0000284 and circ_0072088) can promote lung cancer development via regulating different miRNAs 9,10 . In this research, we aim to explore a new circRNA that is related to lung cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Ling Liu et al reported that miR-377-3p was downregulated in cisplatinresistant osteosarcoma cells and tissues [24], which enlightened us to choose miR-377-3p for further investigations. In addition, miR-377-3p functioned as a tumor suppressor to hamper the development of multiple cancers, such as breast cancer [25], gastric cancer [26], ovarian cancer [27] and NSCLC [28][29][30]. Interestingly, miR-377-3p regulated drug resistance in cancer treatment, and Ling Liu et al reported that miR-377-3p participated in the regulation of cisplatinresistance in osteosarcoma [24], but the role of miR-377-3p in regulating cisplatin-sensitivity in NSCLC is still unknown.…”
Section: Introductionmentioning
confidence: 99%